STRATEGI KOMUNIKASI HUMAS PEMERINTAH KABUPATEN SIMALUNGUN DALAM MENINGKATKAN CITRA PEMERINTAH KABUPATEN SIMALUNGUN - Fitri Arinita Haloho; Besti Rohana Simbolon; Elok Perwirawati (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Darma Agung, 2021)
Public relations plays an important role in every institution because public relations is one of the strategies in shaping the company's image, both positive and negative images. In shaping the image of an institution, public relations usually has a broad relationship. This study aims at determining how the strategy of public relations communication and to find out how the barriers of public relations in the Department of Communication and Information of the Government of Simalungun Regency in shaping the image of government. This type of research uses a qualitative descriptive approach. The results of this study indicate that the public relations communication strategy in the Department of Communication and Information of the Simalungun Regency Government is to carry out two communications, namely internal communication and external communication. Barriers to public relations in the Department of Communication and Information of the Simalungun Regency Government are inadequate resources, large costs and difficulties in creativity. To achieve the objectives of the Simalungun Regency Government's Communication and Information Office in shaping the image of the government, it requires hard work, high discipline, professional skills and expertise in the field of public relations.